Update Breast Cancer 2019 Part 3 - Current Developments in Early Breast Cancer: Review and Critical Assessment by an International Expert Panel - Kolberg, Hans Christian; Schneeweiss, Andreas; Fehm, Tanja N.; Wöckel, Achim; Huober, Jens; Pontones, Constanza; Titzmann, Adriana; Belleville, Erik; Lux, Michael P.; Janni, Wolfgang; Hartkopf, Andreas D.; Taran, Florin Andrei; et al. (Geburtshilfe und Frauenheilkunde, 2019)
The treatment of breast cancer patients in a curative situation is special in many ways. The local therapy with surgery and radiation therapy is a central aspect of the treatment. The complete elimination of tumour cells at the site of the primary disease must be ensured while simultaneously striving to keep the long-term effects as minor as possible. There is still focus on the continued reduction of the invasiveness of local therapy. With regard to systemic therapy, chemotherapies with taxanes, anthracyclines and, in some cases, platinum-based chemotherapies have become established in the past couple of decades. The context for use is being continually further defined. Likewise, there are questions in the case of antihormonal therapy which also still need to be further defined following the introduction of aromatase inhibitors, such as the length of therapy or ovarian suppression in premenopausal patients. Finally, personalisation of the treatment of early breast cancer patients is also being increasingly used. Prognostic tests could potentially support therapeutic decisions. It must also be considered how the possible use of new therapies, such as checkpoint inhibitors and CDK4/6 inhibitors could look in practice once study results in this regard are available. This overview addresses the backgrounds on the current votes taken by the international St. Gallen panel of experts in Vienna in 2019 for current questions in the treatment of breast cancer patients in a curative situation.
CRIS-Team Scopus Importer:2019-06-04
Keywords: adjuvant therapy; early breast cancer; neoadjuvant therapy; St. Gallen panel of experts